Partial molecular characterization of begomoviruses isolated from weeds collected in tomato crops in the southeast of Valle del Cauca, Colombia (2020)
Weeds are a source of new viruses but are often neglected during diversity studies. Eleven weed samples previously were collected along the edges of tomato crops in four municipalities (Florida, Ginebra, Cerrito and Candelaria) in the southeast of Valle del Cauca. These samples were positive for begomoviruses, but their molecular characterization had not been done until now. For each sample, DNA fragments were cloned, sequenced and analyzed. Nucleotide sequence analysis of viral fragments showed the presence of six different begomoviruses: two viruses isolated from Lantana camara, Desmodium sp. and Amaranthus dubius, which were previously identified as potato yellow mosaic virus (PYMV) and passionfruit leaf distortion virus (PLDV), respectively; four viruses isolated from L. camara, A. dubius, Rivina humilis, Desmodium sp., Rhynchosia minima, Hybanthus attenuatus, Verbena sp., Croton hirtus and Caesalpinia sp., showed the highest nucleotide sequence identity (89%) with the bean chlorotic mosaic virus (BChMV), datura leaf distortion virus (DaLDV) and rhynchosia golden mosaic Yucatan virus (RhGMYV). The cloned virus fragments isolated from these weeds could be new begomoviruses which have not been previously reported before, according with the ICTV species demarcation criteria established for the Begomovirus genera (≥91 % sequence identity). In this study, mixed infections of begomoviruses were founded in Desmodium sp. and A. dubius. Finally, this paper reports for the first time the identification of three alternative begomovirus weeds: A. dubius for PYMV and L. camara and Desmodium sp. for PLDV, both viruses which infect tomato and passion fruit crops, respectively.